Character association in paprika (Capsicum annuum/i L.)1 - V Chenga Reddy, D Srihari, A Siva Sankar, S Surya Kumari, K Uma Jyothi,; Ravi Sankar, C (Journal of Spices and Aromatic Crops, 2011)
Correlation studies conducted in 94 diverse genotypes of paprika (Capsicum annuum) grown at Lam (Andhra Pradesh) indicated that dry fruit yield plant-1 showed significant and positive association with plant height, plant spread, number of fruits plant-1, fruit girth, seeds fruit-1 and capsanthin content. Path coefficient studies revealed that number of fruits plant-1 had the highest positive direct effect on dry fruit yield plant-1. Number of fruits plant-1, plant height, plant spread, number of seeds fruit-1, days to maturity and capsanthin content (in the given order) were important yield and quality components having direct bearing on dry fruit yield and hence can be considered while breeding for improved yield in paprika.